The Influencers’ Language on Instagram and Twitter Captions - Nurfausyahbani, Hermayanti Rahma; Setiawan, Dedy (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
The major objective of this study is to analyze grammatical errors found on Instagram and Twitter captions. It is intended to recognize the most common grammatical errors so that we can be aware of the language that we use. The present study applies the theory of Dulay et al (1982) which divides errors into four types: omission, addition, misinformation, and misordering. Since all of the data are in the form of text, a method of textual analysis was applied to analyze the data. The data under analysis are taken from the captions by influencers using English on Instagram and Twitter. The result of the study showed there were 152 errors found from 100 captions and they were classified into misinformation (46%), misordering (3%), addition (16%), and omission (35%). The errors were also classified into grammatical units. Those errors in grammatical units are subject-verb agreement with a total of 16 errors, singular-plural with 15 errors, tense/verb form with 31 errors, word form with 23 errors, capitalization with 28 errors, apostrophe error with 25 errors, missing comma with six errors, article usage error with three errors, wrong/missing preposition with four errors, and word use error with two errors. The most grammatical error that frequently occurs in the Instagram caption is tense/verb with 23 (22%) occurrences and a total of 17 (30%) occurrences of apostrophe errors on Twitter.